Beyond Tiananmen : the politics of U.S.-China relations, 1989-2000 - Suettinger, Robert (Brookings Institution Press, 2003)
Suettinger sees the Tiananmen Square masacre as a turning point in US-China affairs. He traces the bilateral relationship since that time, focusing particular on the internal political factors that shaped relations between the US and China between 1989 and the end of the Clinton presidency in 2000.